Uma nova interface para a inclusão digital na terceira idade - Moro, Gláucio Henrique Matsushita (2010)
This essay discusses the current technology aspect and its simplification through usability techniques aiming to assist the cognitive process of divide people, focused on seniors. Believing that information technology, currently available, is not accurate for certain groups such as elderly community. Based on the hypermedia and network concept of Pierre Lévy and Lúcia Leão; the innovative precepts and poetic interface of Giselle Beiguelman, and reflections on the maturity of Vitória Kachar, develops an argument about the influence of the technology in a panorama of coexistence of different cultural environments. Proposing an interface consistent to the elderly profile, it discusses audience particularities and evaluates their relationship with the existing technological content. Considering Jakob Nielsen s usability recommendations, connects important aspects to develop a project focusing on the elderly audience, identifying the essential elements in a network environment. It analyzes case studies of sites targeted to senior people, classifying them under the criteria of understandability, and operability. Finally, it proposes alternatives for the interface and information architecture for personal computers and mobile devices, designed for the universe of senior people